Analysis of Students’ Numeracy Skills in Solving Problems on Fractional Materials at SD Muhammadiyah 1 Menganti - Mulyasari, Enis; Nugraheni, Liknin; Prayitno, Lydia Lia (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
Numeracy ability is the benchmark of education in Indonesia. This study used a qualitative descriptive method to describe students’ numeracy abilities based on their initial mathematical abilities, categorized as high, medium, and low. The subjects were three students who represented each level of initial mathematics ability, namely high, medium, and low of 5th grade A from SD Muhammadiyah 1 Menganti, Data were collected through tests, interviews, and documentation and were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results show that students with high initial mathematical ability met all three numeracy indicators, those with medium initial ability met two indicators, and those with low initial ability met only one numeracy indicators.